Severe obesity in children as an independent risk factor for perioperative respiratory adverse events during anaesthesia for minor non-airway surgery, a retrospective observational study. (June 2019) - Raghavan, Kavitha; Moo, Daphne Xin Ying; Tan, Zihui
Purpose: The purpose of this article is to quantify grades of obesity and their independent effects on perioperative adverse events in children having ambulatory minor non-airway surgery. Methods: After obtaining ethics committee approval, we selected every tenth child aged 2 to 16 years who was identified as having been a day case between January 2012 and December 2014. Weight groups were defined based on age- and gender-specific body mass index (BMI) cutoff points. A sample size of 1102 was calculated to demonstrate a three-fold increase in the primary outcome measure, perioperative respiratory-airway adverse events, among obese children, with a power of 80% and an alpha error of 5%. Chi-squared and Fisher exact tests were used to compare proportions, and independent sample t tests were used to compare means. Results: Severely obese children had a significantly higher incidence of perioperative respiratory-airway adverse events when compared to normal-weight children despite no difference in respiratory and other comorbidity. Obese children had higher prevalence of overall medical comorbidities and obstructive sleep apnoea when compared to normal-weight children and there was no significant difference in the incidence of perioperative respiratory-airway adverse events and other outcome measures between obese and normal-weight children. Conclusions and recommendations: Severely obese children have a higher risk of perioperative respiratory-airway adverse events even during minor non-airway surgery despite absence of medical comorbidities. We recommend the use of age- and sex- specific BMI cutoffs or BMI percentile charts to identify children who are severely obese to anticipate and prevent major respiratory adverse events.